Pementasan Jejak Orok Sebagai Media Komunikasi Massa: Tinjauan Sosiologi Teater - Rinaldi, Dias Rehan; Ranteallo, Ikma Citra; Kamajaya, Gede (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Theater is a branch of art that focuses on the realm of performance that cannot be separated from the reflection of people's lives so that theater has a role as an archive in elaborating various phenomena along with the times. Art performances can be developed as a medium of mass communication, one of which is by holding the Jejak Orok performance which is engaged in theater at UKM Teater Orok Noceng Udayana University. Before conveying a message in a theater performance, you can consider various things, especially in holding a performance that has a variety of activities and preparation processes that must think carefully about the decision to be able to hold a theater performance that is traveling to a number of places. This research uses a Qualitative approach with an explorative descriptive type. The Sociology of Theatre theory by Riccioni and Shevtsova is used as a scalpel to analyze the performance of Jejak Orok as a mass communication medium. Riccioni and Shevtsova's sociology of theater emphasizes the importance of four elements in theater performances. Students who participate in UKM Teater Orok Noceng choose to hold the Jejak Orok performance as a mass communication medium, namely this view uses theater performances to become a medium in conveying messages to the public. It is concluded that the Jejak Orok performance in 2022 has the benefit of conveying messages derived from the results of reality reflection to be channeled through various theatrical performances, such as drama performances, monologue performances, and poetry musicalization performances. It is suggested that in the implementation of the Jejak Orok program carried out by each committee member to prioritize the preparation of performance training and the fulfillment of the needs of supporting equipment for the performance to be more closely examined in order to hold an optimal theater performance.